Understanding and overcoming hybrid lethality in seed and seedling stages as barriers to hybridization and gene flow - He, Hai; Shiragaki, Kumpei; Tezuka, Takahiro (Frontiers in Plant Science, 2023)
Hybrid lethality is a type of reproductive isolation barrier observed in two developmental stages, hybrid embryos (hybrid seeds) and hybrid seedlings. Hybrid lethality has been reported in many plant species and limits distant hybridization breeding including interspecific and intergeneric hybridization, which increases genetic diversity and contributes to produce new germplasm for agricultural purposes.Recent studies have provided molecular and genetic evidence suggesting that underlying causes of hybrid lethality involve epistatic interaction of one or more loci, as hypothesized by the Bateson-Dobzhansky-Muller model, and effective ploidy or endosperm balance number. In this review, we focus on the similarities and differences between hybrid seed lethality and hybrid seedling lethality, as well as methods of recovering seed/seedling activity to circumvent hybrid lethality. Current knowledge This is a provisional file, not the final typeset article summarized in our article will provides new insights into the mechanisms of hybrid lethality and effective methods for circumventing hybrid lethality.